The potential of tRF-21-U0EZY9X1B plasmatic level as a biomarker of children with obstructive sleep apnea-hypopnea syndrome - Yanbo Lu; Qiang Fu; Xiaohong Cai; Yijing Shen; Junhua Wu; Haiyan Qiu (BMC, 2023)
Abstract Purpose We investigated changes in plasma transfer RNA related fragments (tRF) in children with obstructive sleep apnea-hypopnea syndrome (OSAHS) and the potential value as a disease marker. Methods Firstly, we randomly selected five plasma samples from the case group and the control group for high-throughput RNA sequencing. Secondly, we screened one tRF with different expression between the two groups, amplified it by quantitative reverse transcription-PCR (qRT-PCR) and sequenced the amplified product. After confirming that the qRT-PCR results were consistent with the sequencing results and the sequence of the amplified product contained the original sequence of the tRF, we performed qRT-PCR on all samples. Then we analyzed the diagnostic value of the tRF and its correlation with some clinical data. Results A total of 50 OSAHS children and 38 control children were included in this study. There were significant differences in height, serum creatinine (SCR) and total cholesterol (TC) between the two groups. The plasma expression levels of tRF-21-U0EZY9X1B (tRF-21) were significantly different between the two groups. Receiver operating characteristic curve (ROC) showed that it had valuable diagnostic index, with area under the curve (AUC) of 0.773, 86.71% and 63.16% sensitivity and specificity. Conclusions The expression levels of tRF-21 in the plasma of OSAHS children decreased significantly which were closely related to hemoglobin, mean corpuscular hemoglobin, triglyceride and creatine kinase-MB, may become novel biomarkers for the diagnosis of pediatric OSAHS.